(untitled) (Texas Journal of Agriculture and Biological Sciences, 2022)
The effect of irrigation and fertilizer rates on productivity in the cultivation of cabbage in resowing has been studied. In the experiment, the average mass of cabbage in all variants was in the range of 3.26-2.70 kg. Productivity: On average 65.6 t/ha when mineral fertilizers are applied at 70-70% control irrigation regime (N150P150K100 kg/ha) in the Saratoni variety at 80-80% irrigation regime and (N250P150K100 kg/ha) (81.1 t/ha) was 23.6% higher than the control, and 113.0 and 126.7% higher than the control in the hybrid W61-19 F1 at 80-80% irrigation regime in both fertilization rates. In increasing the yield, the importance of irrigation was stronger than that of mineral fertilizers. Profitability was 37.8-51.4% for the Saratoni variety and 45.7-61.6% for the W61-19 F1 hybrid